Differences In Interest And Student Learning Outcomes With Role Playing And Teams Games Tournament Learning Models - Damanik, Irda Ayuna; Yahfizham; Siregar, Tanti Jumaisyaroh (Yana Research, 2023)
This study aims to determine differences in interest and student learning outcomes with the role playing learning model and team games tournament students of MAN 1 Medan. Based on the results of the data and discussion obtained: 1) There are differences in interest and learning outcomes of students who are taught using the role playing learning model with the team games tournament learning model as evidenced by the analysis of variance test (ANAVA) obtained a value of Fcount = 19.213 and a value in Ftable = 3.960. Which states Fcount > Ftable. 2) There are differences in the learning interests of students who are taught using the role playing learning model with the team games tournament learning model as evidenced by the analysis of variance test (ANAVA) obtained the value of Fcount = 19.213 and the value on Ftable = 4.000 which states Fcount>Ftable . 3) There are differences in the learning outcomes of students who are taught using the role playing learning model with the team games tournament learning model as evidenced by the analysis of variance test (ANOVA) obtained a value of Fcount = 8.247 and a value in Ftable = 4.000. Which states Fcount > Ftable.